Heterotopic Pancreatic Tissue Located in the Gallbladder Wall. A Case Report - Gucer, Hasan; Bagci, Pelin; Coskunoglu, Esra Zeynep; Karadag, Cetin (JOP. Journal of the Pancreas, 2011)
Context Heterotopia of the pancreas can be defined as the presence of pancreatic tissue in an abnormal location without any continuity with the main body of the pancreas. Heterotopic pancreatic tissue located in the gallbladder is a rare entity. Despite being a congenital condition, it takes years for heterotopic pancreas to become symptomatic. Case report An 80-year-old male patient presented to our hospital with a two-week history of abdominal pain, nausea and vomiting aggravated after meals. Abdominal ultrasonography revealed minimal wall edema and small grain-sized gallstones in the gallbladder. The patient was hospitalized and laparoscopic cholecystectomy was performed for acute cholecystitis. Pathologic examination showed a 6 mm nodular mass of pancreatic tissue in the gallbladder wall, comprised mainly of ductal and acinic structures and a few endocrine cells. Conclusion We found this case of pancreatic heterotopia worth reporting because of its rare incidence. Image: Nodular lesion in the subserosal adipose layer of the gallbladder.